Impact of the Proximity of Septic Tanks on the Bacteriological Quality of Well Water from Private House-holds in Ado Ekiti, Nigeria - , E. I. Oluwasola; , O. A. Okunade; , K. Adesina (Archives of Current Research International, 2017)
This study evaluated the effects of the proximity of septic tank on the bacteriological quality of domestic well water of some private house-holds in “Aba Erinfun”, Ado Ekiti, Ekiti State, Nigeria. Twenty (20) samples of private house-holds well water at different locations in the community were analysed for total bacteria count, total coliform count and characterization of isolates. The distance between the wells and the nearest septic tanks ranged from 2.74 m - 42.90 m. Total viable count ranged from 2.4 - 25.4 105 cfu/ml while that of coliform count was 0 - 12.0 105 cfu/ml. The Isolates characterized and identified in the water samples include Escherichia coli, Bacillus spp, Staphylococcus spp and Pseudomonas spp. These results showed that the distance between septic tanks location and water wells has significance in terms of bacterial pollution of the well water. However, other factors like population density, environmental hygiene and ringing/non ringing of wells may also affect the quality of well water. Irrespective of the distance of the water wells from the nearest septic tank, the presence of coliform organism was noticed.